2020
DOI: 10.3390/en13040947
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Solar Thermoelectric Power-Harvesting Device Based on an All-Glass Solar Heat Transfer Pipe and Gravity-Assisted Heat Pipe with Recycling Air Cooling and Water Cooling Circuits

Abstract: For the purpose of collecting solar radiation for energy conversion and utilization and improving the output performance of thermoelectric power-generation components, a new solar thermoelectric conversion device based on an all-glass solar heat transfer pipe and gravity-assisted heat pipe with recycling air cooling and water cooling circuits is designed. The uniqueness of the device lies in the combination of gravity-assisted heat pipes with excellent thermal conductivity and a direct air-cooled mode, a fin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The heat energy generated by the heat source is accepted by the hot side of the heat-energy absorbing TEG module in the form of heat flow. According to [12] and [16], the accepted heat energy HG…”
Section: A Energy Balance Of Tegmentioning
confidence: 99%
See 2 more Smart Citations
“…The heat energy generated by the heat source is accepted by the hot side of the heat-energy absorbing TEG module in the form of heat flow. According to [12] and [16], the accepted heat energy HG…”
Section: A Energy Balance Of Tegmentioning
confidence: 99%
“…The second situation is when the TEG module is in contact with the heat source through the heat-transfer medium and absorbs heat energy from the heat-transfer medium and converts the heat energy into electrical energy. Pure copper blocks were used by Zhang, Z. et al in thermoelectric energy conversion systems by virtue of their good heat-transfer characteristics in the heat-transfer medium, thereby achieving high-performance outputs in terms of thermoelectric energy conversion output [14]- [16]. Tang, S. M. et al used thermally conductive copper blocks to transfer the heat generated by heat pipes to the hot end of the TEG and obtained an output power of 183.2 watts and an output voltage of 42.2 V [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lv et al devised a solar thermoelectric power generator with a micro-channel heat pipe and tube for cooling water, outputting electrical power and heat energy simultaneously [19]. Zhang et al chose a water-cooling circuit to keep the cold side of the thermoelectric module stable [20,21]. The above examples clearly show that the cooling method of a thermoelectric conversion system plays an important role in power generation, and further study should be carried out to acquire a stable and high-performance thermoelectric energy supply.…”
Section: Introductionmentioning
confidence: 99%
“…However, the design of the cold side is also an important issue, as Rad et al [14] found when analyzing two different modes of heat dissipation (air vs. liquid). Very recently, Zhang et al [23] investigated the consequences of using different passive strategies to cool a STEG, with the solar-driven thermosyphon effect of water being the most effective. However, there is another type of STEG design and the main feature is that it directly dissipates heat into the soil so as to have an almost constant temperature bath in one of TEG's faces [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%